2022
DOI: 10.3389/fpls.2022.958138
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early quassinoid biosynthesis in the invasive tree of heaven (Ailanthus altissima) confirms evolutionary origin from protolimonoids

Abstract: The tree of heaven, Ailanthus altissima (MILL.) SWINGLE, is a globally invasive plant known to secrete allelopathic metabolites called quassinoids. Quassinoids are highly modified triterpenoids. So far, nothing has been known about the biochemical basis of quassinoid biosynthesis. Here, based on transcriptome and metabolome data of Ailanthus altissima, we present the first three steps of quassinoid biosynthesis, which are catalysed by an oxidosqualene cyclase and two cytochrome P450 monooxygenases, resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Many recent examples demonstrate that co-expression analysis is a helpful tool to discover novel biosynthetic genes. [24][25][26][27] During our recent discovery of the genes required for melianol (8) biosynthesis in A. altissima based on de novo transcriptome sequencing, [23] we observed that these genes were highly co-expressed. We therefore expected that further, yet unknown genes involved in triterpenoid biosynthesis may share a similar expression profile.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many recent examples demonstrate that co-expression analysis is a helpful tool to discover novel biosynthetic genes. [24][25][26][27] During our recent discovery of the genes required for melianol (8) biosynthesis in A. altissima based on de novo transcriptome sequencing, [23] we observed that these genes were highly co-expressed. We therefore expected that further, yet unknown genes involved in triterpenoid biosynthesis may share a similar expression profile.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore expected that further, yet unknown genes involved in triterpenoid biosynthesis may share a similar expression profile. We therefore searched our A. altissima expression data from previous work [23] for gene candidates co-expressed with the first three genes in the pathway. To facilitate visual analysis of the underlying multidimensional dataset, we employed self-organising map (SOM) analysis (Figure 2), which arranges large numbers of transcripts into clusters based on their expression profile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Limonoids are highly oxidised, modified and truncated triterpenoids; one of the most well-known limonoids is the eponymous compound limonin (18), which contributes to the bitter taste of citrus products (Figure 6C) [104]. The first steps of limonoid biosynthesis were recently explored by functional characterisation in heterologous hosts [29,[105][106][107]. There, CYP enzymes MaCYP71CD2 and MaCYP71BQ5 from Melia azedarach initiate the ring formation on the side chain of the triterpene precursor tirucalla-7,24-dien-3β-ol (19) in a sequential manner.…”
Section: Recent Examples Of Triterpenoid and Steroid Cytochrome P450 ...mentioning
confidence: 99%